2022
DOI: 10.3390/ijms232415969
|View full text |Cite
|
Sign up to set email alerts
|

Role of Oxidative Stress in Peyronie’s Disease: Biochemical Evidence and Experiences of Treatment with Antioxidants

Abstract: Background: Peyronie’s disease (PD) is a chronic inflammatory condition affecting adult males, involving the tunica albuginea of the corpora cavernosa of the penis. PD is frequently associated with penile pain, erectile dysfunction, and a secondary anxious–depressive state. The etiology of PD has not yet been completely elucidated, but local injury is generally recognized to be a triggering factor. It has also been widely proven that oxidative stress is an essential, decisive component in all inflammatory proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 170 publications
1
13
0
Order By: Relevance
“…According to this hypothesis, CPC would favor traumatic events of different degrees of severity during coitus (36)(37)(38). In fact, repeated intercoital thrusts can cause microtraumas in the context of the tunica albuginea of the corpora cavernosa, thus giving rise to the events underlying the formation of the plaque: delamination of the tunica albuginea, micro-hematoma, accumulation of fibrin, recruitment of macrophages, lymphocytes, platelets and fibroblasts, production of pro-inflammatory cytokines, and production and accumulation of collagen (26,39). The present study was aimed at studying the relationship between a history of congenital penile curvature and Peyronie's disease.…”
Section: Psychological Consequences Of Congenital or Acquired Penile ...mentioning
confidence: 99%
“…According to this hypothesis, CPC would favor traumatic events of different degrees of severity during coitus (36)(37)(38). In fact, repeated intercoital thrusts can cause microtraumas in the context of the tunica albuginea of the corpora cavernosa, thus giving rise to the events underlying the formation of the plaque: delamination of the tunica albuginea, micro-hematoma, accumulation of fibrin, recruitment of macrophages, lymphocytes, platelets and fibroblasts, production of pro-inflammatory cytokines, and production and accumulation of collagen (26,39). The present study was aimed at studying the relationship between a history of congenital penile curvature and Peyronie's disease.…”
Section: Psychological Consequences Of Congenital or Acquired Penile ...mentioning
confidence: 99%
“…In individuals not genetically susceptible to the disease, the hematoma is typically reabsorbed. However, in individuals with a genetic predisposition, the hematoma causes local recruitment of inflammatory cells and pro-inflammatory cytokines, resulting in the formation of chronic inflammatory tissue that subsequently progresses to fibrosis [ 27 , 28 , 29 ]. Over the past 20 years, research has shown that oxidative stress (OS) plays a critical role in plaque formation and in the progression of PD [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…PD presents in a unifocal manner (single plaque) in the majority of cases (78–84%) but can also occur in multiple areas of the penile corpora cavernosa [ 9 ]. Over the last two decades, oxidative stress (OS) has proven to be very important and crucial for plaque formation and the evolution of the disease itself [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The disease presents and evolves in two phases.…”
Section: Introductionmentioning
confidence: 99%
“…The second phase of PD consists of the stabilization of PD with the consequent stabilization of the deformation and the disappearance of pain. This is the phase of the disease where surgical intervention is indicated (corporoplasty, plaque incision, and/or implantation of penile prosthesis) [ 7 , 19 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Peyronie’s fibrous plaque can calcify in approximately 20–36% of cases [ 47 , 48 ].…”
Section: Introductionmentioning
confidence: 99%